Artrópodos associados à cultura da nogueira-pecã [Carya illinoinensis (Wangenh.) K. Koch] no Rio Grande do Sul - Boscardin, Jardel (2016)
In recent years there has been an increase in the area planted with Carya illinoinensis (Wangenh.) K. Koch (Junglandaceae), mainly in southern Brazil. The extent to which the cultivation of pecan growing in the country, it is necessary that science and technology to track such progress. This study aimed to evaluate the arthropod fauna associated with pecans in Rio Grande do Sul. Therefore, an experiment was conducted in a planting of C. illinoinensis, with approximately 1.2 hectares in spacing 7 m x 7 m, subjected to different preparations and holes soil, in Santa Maria, RS. Was used delineation of randomized blocks with five blocks and four treatments: planting small pit 20 cm x 60 cm (Cp); using more grid subsoiler leveler and small pit (Scp); use rotary hoe and small pit (Ecp); and planting in large pit 40 cm x 60 cm (Cg). Eight collected were performed with pitfall traps model "pitfall" in every season, summer 2014 to spring 2015; 18 fortnightly collections, from March 2014 to May 2015, with yellow sticky traps in the areas of treatment and the surrounding area (En) and 13 collections, fortnightly, with pantry network from November 2014 to May 2015, only in planting. In October 2012, plantations were visited in Tunas and Mata, RS, for surveys of trees attacked by borers and in March 2014 and 2015 were performed manual collection of phytophagous bugs attacking pecans fruit in plantations located in the city of Paraíso do Sul, RS; the material collected in both areas was taken to the laboratory for screening. For the area with soil tillage and cabling, it was found that Ecp treatment had the lowest values of diversity and evenness for epigeic animals (H´ = 0.93 and J´= 0.36) and coleopterofauna (H´ = 1.89 and J´ = 0.66), while Scp and Cg showed the highest levels, for epigéicos arthropods and Coleoptera, respectively. Diloboderus abderus (Sturm) (Melolonthidae) was the most common species in all areas, occurring only in summers. Was not founded statistical difference in the densities of the species between treatments. Seasonality influences the abundance and richness of epigeic arthropods. For sticky traps was not verified difference between the treatments, and the population acme Monellia caryella (Fitch) (Aphididae) occurred in April 2014, it was the association of the species with Coccinellidae. In the tops of pecan plants were collected 150 taxa, Coleoptera and the order of greater wealth. Diptera, Brachymyrmex admotus (Formicidae) and M. caryella were the highest attendance rate collected with canopy network, having been verified statistical difference between treatments for the abundance and species richness. In Tunas, were found two species of the Corthylus and a Xyleborinus (Curculionidae, Scolytinae), attacking pecan trunk, and in Paraíso do Sul, for the first time was registred species of Leptoglossus stigma (Herbst), L. zonatus (Dallas) (Coreidae) and Loxa deducta Walker (Pentatomidae) attacking C. illinoinensis fruits.